2020
DOI: 10.1016/j.diabres.2020.108514
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to glycemic control in diabetes mellitus patients complying with home quarantine during the coronavirus disease 2019 (COVID-19) epidemic

Abstract: Highlights Glycemic control may be affected during the epidemic of COVID-19. The factors affecting glycemic control in patients with type 2 diabetes included age, education level, glucose monitoring equipment availability, medication adherence and the frequency of self-monitoring of blood glucose. The factor affecting glycemic control in patients with type 1 diabetes was education level. During the pandemic, diabetes self-management educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 23 publications
2
36
1
2
Order By: Relevance
“…Lockdown seems to have produced a greater beneficial effect on females than in males. This is consistent with a Chinese study in which males with T1DM had poorer glycaemic control than females during COVID-19 lockdown [28]; previous findings showed that females with DM, when compared to males, elicited more frequently behaviours aimed at disease prevention, health promotion and symptom recognition [29], which could have been of help in coping with confinement. An increase in glucose monitoring and an improvement in insulin titration during remote working or remote schooling may explain these improvement, as suggested by a study showing an improvement in glucose control only in patients working at home [21]; unfortunately, the information on glucose monitoring and on the proportion of patients on home schooling or working was insufficient to add these variables as moderators.…”
Section: Discussionsupporting
confidence: 91%
“…Lockdown seems to have produced a greater beneficial effect on females than in males. This is consistent with a Chinese study in which males with T1DM had poorer glycaemic control than females during COVID-19 lockdown [28]; previous findings showed that females with DM, when compared to males, elicited more frequently behaviours aimed at disease prevention, health promotion and symptom recognition [29], which could have been of help in coping with confinement. An increase in glucose monitoring and an improvement in insulin titration during remote working or remote schooling may explain these improvement, as suggested by a study showing an improvement in glucose control only in patients working at home [21]; unfortunately, the information on glucose monitoring and on the proportion of patients on home schooling or working was insufficient to add these variables as moderators.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 . In a study from France, 45% of 195 patients with chronic heart disease had a >25% reduction in physical activity and 24% of patients had gained >2kg weight 229 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…[ 10 , 11 ] In addition, there have been several antidiabetic medications for T2DM patients including oral and injectable medications. [ 8 , 12 , 13 ] However, there is limited data about the economics, hospital level and regions on the poor glycemic control among T2DM patients treated with antidiabetic medications in China.…”
Section: Introductionmentioning
confidence: 99%